Get the residency : ASHP's guide to residency interviews and preparation - Caballero, Joshua; Clauson, Kevin A.; Benavides, Sandra (American Society of Health-System Pharmacists, 2019)
"This book will present cogent strategies for targeting residencies, practical tips for each step in the submission and application processes, and preparatory exercises designed to replicate what students face in actual residency interview situations. This book provides a guide to contacting residency directors, submitting a letter of intent and curriculum vita, and approaching professors for letters of recommendation. Pragmatic approaches are used to help students manage the challenges during the onsite visit such as solo and panel interviews, delivering an engaging presentation, and working up an assignment on the spot. The new edition will include navigating PhORCAS, Phase II Match, an enhanced focus on the increasing role of topics including diversity and technology, and editing to make it more current including adding a section on maintaining mental health during and after the process and selecting a program based on personal views"--